English as a Threat for Indigenous Language among Middle Low-Class Society in Java Rural Area: Evidence of Code-Mixing - Rohmani, Diyah Ayu; Setiawan, Slamet (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
The occurrence of Javanese-Indonesian-English code-switching among people in cities is common since the cities are the melting pot of heterogeneous people from different linguistic backgrounds. However, it is alarming when code-switching is performed by middle-class society in rural areas in their daily communication. The fact indicates that rural dwellers are relatively homogenous communities. Given the aforementioned context related to code-switching, this study, therefore, aims to reveal its types, to seek its factors, and to get informants’ understanding of the English terms used. This study used a qualitative method by applying interviews and a simple test to get the data. The finding showed that there are three types of code-switching they are inter-sentential, intra-sentential, and extra-sentential but the intra-sentential one was mostly used by the villagers. Regarding to factors triggering the occurrences of code-switching, the rural dwellers reported that their action was influenced by the interluctor, topic, setting, and function when the conversation took place. Even though the villagers used some English terms in daily communication, they confessed that they are still lack of English understanding. The use of English terms was for a practical purpose as the terms were ready to use instead of looking for their Indonesian equivalent. In addition, the English expressions were easily understood by the involved parties in a communication. When this phenomenon goes on and on and is passed to successor generations, it is not impossible that the English language emerges to be the threat of ethnic language in the rural area.